Plan de negocios para el diseño e implementación de una aplicación para teléfonos móviles que facilita las compras en los supermercados - Quispe Velásquez, Merssy Luisa (2019)
This study investigates the technical, economic and financial feasibility of an application for smartphones that allows purchases in supermarkets, being its main differentiating factor, the ability to have budgets for the entire shopping list in the nearest supermarkets, and so the customer can choose the option that suits him/her. To do this, a survey was applied to heads of families, of the B socioeconomic level of Metropolitan Lima, identifying two types of users: early adopters and followers, the first group being willing to try new technologies, they will use the application during the first year of operation. It is concluded that the project is feasible with a high potential to be scalable, given the increase and boom in the intensive use of applications.